2013
DOI: 10.1371/journal.pone.0077892
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Antigenic Variants at the Antigenic Site Sb in Pandemic A(H1N1)2009 Influenza Virus in Japan Detected by a Human Monoclonal Antibody

Abstract: The swine-origin pandemic A(H1N1)2009 virus, A(H1N1)pdm09, is still circulating in parts of the human population. To monitor variants that may escape from vaccination specificity, antigenic characterization of circulating viruses is important. In this study, a hybridoma clone producing human monoclonal antibody against A(H1N1)pdm09, designated 5E4, was prepared using peripheral lymphocytes from a vaccinated volunteer. The 5E4 showed viral neutralization activity and inhibited hemagglutination. 5E4 escape mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
3
21
1
Order By: Relevance
“…These findings concur with other studies where 129D and 186D were found in H1N1pdm09 viruses already egg adapted at 222/223 [1,11,12] or 191 [12, 13], and we conclude that (like reside 119) residues 129 and 186 are not independent egg adaptation loci for A/Christchurch/16/2010.…”
Section: Discussionsupporting
confidence: 94%
“…These findings concur with other studies where 129D and 186D were found in H1N1pdm09 viruses already egg adapted at 222/223 [1,11,12] or 191 [12, 13], and we conclude that (like reside 119) residues 129 and 186 are not independent egg adaptation loci for A/Christchurch/16/2010.…”
Section: Discussionsupporting
confidence: 94%
“…Notably, these 5 novel positions are comparable to those in antigenic site B in H3 virus (24)(25)(26). This site, equivalent to antigenic site Sa and partial site Sb (27,28), is close to the HA receptor binding site and is probably under greater immune pressure than other antigenic sites (29)(30)(31). We examined 1,036 full-length H9 sequences available in GenBank (as of 19 July 2013) by using multiple sequence comparison by log expectation (MUSCLE) (32) and found variations at each of the 9 amino acid positions ( Table 4).…”
mentioning
confidence: 77%
“…Most heterosubtypic crossneutralizing HuMAb have been reported to recognize epitopes located mainly in the most conserved HA stem region [7,10,14,23]. Also, a few HuMAbs that target relatively conserved epitopes adjacent to or overlapping the RBS in the head region were shown to be subtype-specific [17,25,26]. To our knowledge, 5D7 is the first heterosubtypic neutralizing HuMAb that targets a conserved epitope distinct from the RBS in the HA globular head region.…”
Section: Discussionmentioning
confidence: 94%
“…Escape mutants were isolated by culturing A/Suita/1/2009 in the presence of HuMAb, as described previously [17], with minor modifications. Briefly, the virus was incubated with 10-fold diluted HuMAb (to give final concentrations of 5, 0.5 and 0.05 lg/ml) at 37°C for 1 h. MDCK cells in 24-well plates were then inoculated with the mixtures and cultured with DMEM/F12+GlutaMAX-1 (Invitrogen) supplemented with 0.4% BSA, 2 lg/ml acetylated trypsin and antibiotics.…”
Section: Selection Of Escape Mutantsmentioning
confidence: 99%
See 1 more Smart Citation